Efficacy of low-level laser therapy on scar tissue - Freitas, Carla (2014)
Physiotherapy has a very important role in the maintenance of the integumentary system integrity. There is very few evidence in humans. Nevertheless, there are some studies about tissue regeneration using low-level laser therapy (LLLT). Aim: To analyze the effectiveness of LLLT on scar tissue. Methods: Seventeen volunteers were stratified by age of their scars, and then randomly assigned to an experimental group (EG) — n = 9 – and a placebo group (PG) – n = 8. Fifteen sessions were conducted to both the groups thrice a week. However, in the PG, the laser device was switched off. Scars’ thickness, length, width, macroscopic aspect, pain threshold, pain perception, and itching were measured. Results: After 5 weeks, there were no statistically significant differences in any variable between both the groups. However, analyzing independently each group, EG showed a significant improvement in macroscopic aspect (p = 0.003) using LLLT. Taking into account the scars’ age, LLLT showed a tendency to decrease older scars’ thickness in EG. The intervention with LLLT appears to have a positive effect on the macroscopic scars’ appearance, and on old scars’ thickness, in the studied sample. However, it cannot be said for sure that LLLT has influence on scar tissue.